Karakteristik Komunikator Remaja SMA yang Berhubungan dengan Komunikasi Kesehatan Reproduksi di Kota Palembang - Oktarini, Putri Dwi; Etrawati, Fenny (UI Scholars Hub, 2021)
Background. Adolescents are the most vulnerable age to experience unsafe and risky reproductive health problems such as abortion and sexually transmitted infections. One of the efforts made by the government to overcome this is through a peer group approach developed in the Youth Information and Counseling Center (PIK R) as a bridge to the communication process. Objective. This study aims to determine the relationship between the characteristics of high school youth communicators with reproductive health communication in Palembang City in 2018. Method. This study used a cross-sectional design. The sample of this study is 112 high school adolescents whose educational institutions had been exposed to the PIK R in Palembang CIty. The sampling of this study used random cluster sampling. Results. There were 30.4% of reproductive health communication less active in high school adolescents in Palembang City. The characteristics of communicators that influenced reproductive health communication in high school adolescents in Palembang City were knowledge, friendship relationships, information conveying skills, and the role of parents. Conclusion: The need for efforts to improve the quality of members by conducting training for peer educators and peer counselors to strengthen adolescents’ knowledge, attitudes, and skills in providing IEC regarding reproductive health.